Knowing your value : women, money, and getting what you're worth - Brzezinski, Mika. (Weinstein Books, 2010)
Interviews a number of prominent women--including comedian Susie Essman, writer and director Nora Ephron, and TV personality Joy Behar--to reveal how all women can achieve their deserved recognition and financial worth in the modern professional world.